2011
DOI: 10.1086/658990
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy Is Nine-Tenths of the Law: Occupancy Rates Determine the Homogenizing and Differentiating Effects of Exotic Species

Abstract: Biotic homogenization, the loss of local biotic distinctiveness among locations (beta diversity), is a form of global change that can result from the widespread introduction of non-native species. Here, we model this process using only species' occupancy rates--the proportion of sites they occupy--without reference to their spatial arrangement. The nonspatial model unifies many empirical results and reliably explains >90% of the variance in species' effects on beta diversity. It also provides new intuitions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Null and neutral models can be useful for clarifying our thinking (Harris et al. , Xiao et al. ), but deviations from a given null model must be interpreted with care (Roughgarden ).…”
Section: Discussionmentioning
confidence: 99%
“…Null and neutral models can be useful for clarifying our thinking (Harris et al. , Xiao et al. ), but deviations from a given null model must be interpreted with care (Roughgarden ).…”
Section: Discussionmentioning
confidence: 99%
“…Knowing which occurs may allow predictions about whether the presence of non‐native plant species leads to homogenisation or differentiation of herbivorous arthropods in un‐manipulated plant communities (Harris et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…At broader scales, it is important to understand whether herbivores that are able to use non-native plants represent a unique or redundant subset of species across sites. Knowing which occurs may allow predictions about whether the presence of non-native plant species leads to homogenisation or differentiation of herbivorous arthropods in un-manipulated plant communities (Harris et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although N emission rates have decreased and rates of deposition have leveled off or declined in some developed regions such as Europe and the eastern United States (Du et al 2014, Waldner et al 2014, emissions are expected to increase in developing countries (Galloway et al 2008, Liu et al 2013. The potential for the recovery from the impacts of N deposition may be slowed due to the enrichment of ecosystem pools of N (Vinton and Burke 1995), and changes in plant and microbial communities that may enhance rates of N cycling and continue to elevate soil N supply (Bowman and Steltzer 1998, Freedman et al 2016, Choma et al 2017) and resist the re-invasion of the community by the original species by occupying the space (Harris et al 2011). The further along an ecosystem is in the trajectory of impacts described above, including eutrophication and acidification, the less likely that ecosystem is to show recovery once N deposition rates are lowered.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple results from both observational and experimental studies indicate that ecosystem recovery, or the return of biotic composition and ecosystem processes to pre-impacted conditions with decreases in N deposition, occurs slowly or not at all, even after a decade or more of lowered N inputs (Boxman et al 1998, Strengbom et al 2001, Clark et al 2009, and others reviewed in Stevens 2016). The potential for the recovery from the impacts of N deposition may be slowed due to the enrichment of ecosystem pools of N (Vinton and Burke 1995), and changes in plant and microbial communities that may enhance rates of N cycling and continue to elevate soil N supply (Bowman and Steltzer 1998, Freedman et al 2016, Choma et al 2017) and resist the re-invasion of the community by the original species by occupying the space (Harris et al 2011). Furthermore, geochemical changes in the soil such as greater weathering of Al at low soil pH and leaching of soil cations may take decades or more to reverse (Nohrstedt 1998, Wright et al 2001, although some studies have reported significant recoveries of soil base cations within a decade of recovery (H€ ogberg et al 2006).…”
Section: Introductionmentioning
confidence: 99%